Digital Storytelling in the Era of TikTok and Short-From Video Content - Paramita Hapsari, S.Ds, M.Ds, Paramita Hapsari, S.Ds, M.Ds (Akademi Komunikasi SAE Indonesia, 2024)
The research investigates how platforms like TikTok can change the way stories are told in short videos and how that impacts digital videography production methods. Additionally, the study investigates how TikTok's recommendation algorithm affects the distribution and visibility of digital content and their influence on content diversity and inclusion. This study utilizes both qualitative and quantitative approaches. The study looks at the different approaches used by content creators on TikTok, as well as how the platform's algorithm selects and displays content to users. Research shows that TikTok's algorithm driven by user engagement personalizes the viewing experience by displaying content that suits individual preferences. This increases user engagement but also creates